2000
DOI: 10.2486/indhealth.38.289
|View full text |Cite
|
Sign up to set email alerts
|

The Chemiluminescent Response from Human Monocyte-Derived Macrophages Exposed to Various Mineral Fibers of Different Sizes.

Abstract: The aims of the present work were to quantify ability to induce lucigenin-dependent chemiluminescence (CL) from 6-9 day-old human monocyte-derived macrophages exposed to various mineral fibers, and to examine the relationship between ability to induce CL and fiber size. All fiber samples induced the CL response from the cells. The relationship between the number of fibers administered and the CL response was examined on all fiber samples by linear regression. The slope of the regression line supplies an approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…We previously suggested that macrophages non-specifically induce the release of superoxide on exposure to different types of mineral fibers, depending on fiber length; moreover, the increase rate of the ability to induce chemiluminescence (CL) depends on fiber width. We demonstrated a strong correlation between geometric-mean fiber length and the ability to induce CL (largest r 2 = 0.9760) and a negative correlation between geometric-mean fiber width and the increase rate of the ability to induce CL (largest r 2 = 0.7473) in seven types of mineral fibers (Ohyama et al, 2000(Ohyama et al, , 2001. Therefore, we consider that the reactivity of the superoxide response from macrophages not only depends on fiber geometry but also on particle size.…”
Section: Introductionmentioning
confidence: 82%
“…We previously suggested that macrophages non-specifically induce the release of superoxide on exposure to different types of mineral fibers, depending on fiber length; moreover, the increase rate of the ability to induce chemiluminescence (CL) depends on fiber width. We demonstrated a strong correlation between geometric-mean fiber length and the ability to induce CL (largest r 2 = 0.9760) and a negative correlation between geometric-mean fiber width and the increase rate of the ability to induce CL (largest r 2 = 0.7473) in seven types of mineral fibers (Ohyama et al, 2000(Ohyama et al, , 2001. Therefore, we consider that the reactivity of the superoxide response from macrophages not only depends on fiber geometry but also on particle size.…”
Section: Introductionmentioning
confidence: 82%
“…Untersuchungen in vitro in Abwesenheit und Anwesenheit von BEAS2BZellen haben gezeigt, dass lange nadelförmige MWCNT (Durchmesser = 74 nm, Län-ge = 5,7 µm; Durchmesser = 64 nm, Länge = 4 µm) zu einer dosisabhängigen Bildung von bisher nicht identifizierten Radikalen führten (Nymark et al 2014). (Ohyama et al 2000(Ohyama et al , 2001. Bei der Entstehung reaktiver Sauerstoffspezies ist auch die membranständige NADPHOxidase beteiligt, die das Primärprodukt O 2…”
Section: Faseroberflächenreaktivitätunclassified
“…We demonstrated previously a method for comparing the ability to induce lucigenin-dependent chemiluminescence (CL) per fiber from human monocyte-derived macrophages exposed to nine types of mineral fibers of different sizes at the acute phase of the response (20). We observed that the ability to induce CL increased with fiber length at the acute phase of the response, when the mineral fibers were longer than approximately 6 µm.…”
mentioning
confidence: 93%
“…We analyzed the ability to induce CL per fiber of each sample as described previously (20). Briefly, we examined the relation between the estimated number of fibers administered and CL response by linear regression.…”
Section: Mineralmentioning
confidence: 99%
See 1 more Smart Citation